2006
DOI: 10.1007/s10726-006-9020-3
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Computing Devices to Support Mobile Collaboration

Abstract: Collaboration supported by mobile devices has brought advantages for users and also challenges for software developers and mobile computing devices manufacturers. Every kind of device used to support mobile collaboration has strengths and weaknesses depending on the work context where it is used. The idea is to use a specific device when advantages are most relevant and disadvantages do not affect team work. This paper proposes an evaluation framework that helps developers to identify the type of device that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…In contrast to analogue, the digital radio enables to transmit data on a narrow-band, but the rate is limited to 3 kbit/s, which does not allow transmitting much data, like multimedia. Based on empirical studies Guerrero et al (2006) and Peng et al (2007) developed conception frameworks, which determine appropriate devices besides digital radio for certain cooperation contexts. Both frameworks deem tablet PCs and PDAs as the most suitable in terms of mobility.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to analogue, the digital radio enables to transmit data on a narrow-band, but the rate is limited to 3 kbit/s, which does not allow transmitting much data, like multimedia. Based on empirical studies Guerrero et al (2006) and Peng et al (2007) developed conception frameworks, which determine appropriate devices besides digital radio for certain cooperation contexts. Both frameworks deem tablet PCs and PDAs as the most suitable in terms of mobility.…”
Section: Related Workmentioning
confidence: 99%
“…However, in order to articulate information needs, infrastructures are needed. Independent from knowledge about both frameworks for selecting devices for specific contexts (Guerrero et al, 2006;Peng et al, 2007) the interviewees confirmed: "if we're talking about an ideal situation, then I have a smartphone in my patrol car and the officer-in-charge uses a different device that gives him even more functionality" (IM04). Right now the communication path is still via radio, but smartphones are already used for purposes like using Google Maps for satellite views or navigation (I04), because the control centre gives an address and the on-site team often does not know the exact location.…”
Section: Articulation Of Information Needsmentioning
confidence: 99%
“…Although using these applications is better than using paper-based information, they do not support instances for collaboration among the actors involved in the inspection process. In addition, these solutions are based on PDAs, therefore they have several usability problems to do hand-written annotations (Guerrero et al 2006;Ochoa et al 2007). In fact, COIN also runs on PDAs, but our usability tests indicated that platform is not appropriate to support construction inspection processes: PDAs are not comfortable enough to input unstructured and intensive data (Guerrero et al 2006).…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, there are collaborative solutions proposed to support mobile workers in specific settings (André and Antunes 2004;Guerrero et al 2006;MenchacaMendez et al 2004;Muñoz et al 2003;Zurita et al 2005), different to construction management. These proposals have shown to be useful to support particular collaborative processes; however, they were not designed as general solutions, therefore it is not easy to reuse or adapt them.…”
Section: Related Workmentioning
confidence: 99%
“…ColaboQuim is designed on top of a hardware architecture shown in figure 2. This architecture design was based on our previous work [7,8].…”
Section: Colaboquimmentioning
confidence: 99%